Proton transfer reactions of hydrazine‐boranes. (6th January 2015) - Adamson, Aiko; Guillemin, Jean‐Claude; Burk, Peeter
Abstract : Hydrazine‐borane and hydrazine‐diborane contain, respectively, 15.4 and 16.9 wt% of hydrogen and are potential materials for hydrogen storage. In this work we present the gas‐phasecomplexation energies, acidities, and basicities of hydrazine‐borane and hydrazine‐bisborane calculated at MP2/6‐311 + G(d, p) level. We also report the release of dihydrogen from both protonated complexes (ΔGhydrazine‐borane  = −20.9 kcal/mol and ΔGhydrazine‐bisborane  = −27.2 kcal/mol) which is much more exergonic than from analogues amine‐boranes. The addition of the first BH3 to the hydrazine releases 17.1 kcal/mol, and the second addition releases 15.8 kcal/mol. The attachment of BH3 also increases the N―H acidity of hydrazine by 46.3 kcal/mol. It was found that the B―Hdeprotonation leads tointramolecular rearrangement . The basicity values for hydrazine‐borane and ‐bisborane are 180 and 172.8 kcal/mol, respectively. For both complexes the protonation centres are located at the boron moiety. The protonated structure of hydrazine‐bisborane is cyclic and can be described as H2 captured between a negatively charged B―H hydrogen and positive boron (B―HH2B). Atoms in molecules analysis are used to investigate bond paths in concerning structures. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Protonated structure of hydrazine‐bisborane is cyclic and can be described as H2 captured between a negatively charged B―H hydrogen and positive boron (B―HH2B). The H2 release from the structure is strongly excergonic.